Peran Perguruan Tinggi Pesantren dalam Implementasi Literasi Ekonomi - Ahmad Lukman Nugraha; Adib Susilo; Chaerul Rochman (Journal of Islamic Economics and Finance Studies, 2021)
AbstractThis study aims to determine the role of Islamic boarding schools in the application of economic literacy. The research method used is descriptive qualitative. The object of this research is Darussalam Gontor University. The results of this study indicate that Islamic boarding schools in implementing economic literacy carry out several functions; 1) as an educational institution that changes the economic orientation of the community which was originally intended to satisfy wants, to become "sufficient" by meeting needs, 2) as an educational institution that changes a consumptive lifestyle into a moderate lifestyle, 3) as an educational institution that frames human economic activities in the framework of ta'abbudi (worship) which was originally limited to the framework of meeting physical needs, 4) as an educational institution that changes its profit and utility orientation, to an orientation to maximize maslahah, 5) as an educational institution that applies forced learning methods, and finally could be because they are used to it, 6) as an educational institution that applies economic literacy not limited to academic aspects, but non-academic aspects.AbstrakPenelitian ini bertujuan untuk mengetahui peran universitas pesantren dalam penerapan literasi ekonomi. Metode penelitian yang digunakan adalah deskriptif kualitatif. Objek penelitian ini adalah Universitas Darussalam Gontor. Hasil penelitian ini menunjukkan bahwa universitas pesantren dalam pelaksanaan literasi ekonomi menjalankan beberapa fungsi; 1) sebagai lembaga pendidikan yang mengubah orientasi ekonomi masyarakat yang semula dimaksudkan untuk memuaskan keinginan, menjadi "cukup" dengan memenuhi kebutuhan, 2) sebagai institusi pendidikan yang mengubah gaya hidup konsumtif menjadi gaya hidup moderat, 3) sebagai lembaga pendidikan yang membingkai kegiatan ekonomi manusia modern dalam kerangka ta'abbudi (ibadah) yang semula terbatas pada kerangka pemenuhan kebutuhan fisik, 4) sebagai lembaga pendidikan yang mengubah orientasi berorientasi keuntungan dan utilitas, menjadi orientasi memaksimalkan maslahah, 5) sebagai institusi pendidikan yang menerapkan metode pembelajaran secara paksa, dan akhirnya bisa karena mereka sudah terbiasa, 6) sebagai lembaga pendidikan yang menerapkan literasi ekonomi tidak terbatas pada aspek akademik, tetapi aspek non-akademik.